New species-group taxa of Glossoscolex (Clitellata: Glossoscolecidae) from Rio Grande do Sul, Brazil - Bartz, Marie L.c.; James, Samuel W.; Steffen, Gerusa P.k.; Antoniolli, Zaida; Steffen, Ricardo B.; Brown, George G. (Zootaxa, 2018)
Five new species-group taxa of Clitellata of the genus Glossoscolex from Rio Grande do Sul State, Brazil are described in this paper: Glossoscolex (Glossoscolex) riograndensis n. sp. has three subspecies, G. (G.) riograndensis riograndensis, G. (G.) riograndensis pollulus n. ssp., G. (G.) riograndensis nativus n. ssp. The two other new species are named G. (G.) pastivus n. sp., and G. (G.) pampas n. sp. All new species are part of the truncatus species group within the subgenus, characterized by the presence of male pores in segment xvii. A single unnamed specimen, also described here, is deemed to belong to a sixth new species-group taxon of the truncatus group. A tabular character comparison of the new taxa and known and morphologically similar species is given. Information on the habitat, such as vegetation cover and soil characteristics, is given as well. G. (G.) r. riograndensis and G. (G.) r. pollulus had an unusual storage of sperm in the nephridia. Histological sections were performed to verify it.